A single preoperative pain neuroscience education: Is it an effective strategy for patients with carpal tunnel syndrome?. (May 2019) - Núñez-Cortés, Rodrigo; Espinoza-Ordóñez, César; Pommer, Paula Pino; Horment-Lara, Giselle; Pérez-Alenda, Sofía; Cruz-Montecinos, Carlos
Abstract: Patients undergoing carpal tunnel release surgery may continue to experience pain despite the intervention. This symptom may be modulated by psychosocial factors including depression, catastrophic thinking, and kinesiophobia. Pain neuroscience education (PNE) has been found to be effective when combined with therapeutic exercise in patients with chronic pain, but this strategy has not been evaluated in patients with persistent hand pain. The findings of this study indicate that a single preoperative PNE session in combination with therapeutic exercise does not provide added benefits in comparison to standard preoperative care plus therapeutic exercise. Future studies should evaluate if patients with carpal tunnel release are additionally benefited by the incorporation and consequent behavioural changes of more PNE sessions to multimodal treatment.